1992
DOI: 10.1161/01.res.70.6.1313
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide mediates nitroglycerin and sodium nitroprusside-induced vasodilation in feline cerebral arterioles.

Abstract: The cerebral vasodilator response induced by topical nitroglycerin and nitroprusside was examined in cats equipped with cranial windows for the observation of the cerebral microcirculation. In cats subjected to chronic unilateral trigeminal ganglionectomy, the vasodilator responses to nitroprusside and nitroglycerin were markedly depressed on the denervated side. Application of a selective calcitonin gene-related peptide (CGRP) antagonist [CGRP(8-37)] on the innervated side reduced the response to nitrodilator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
120
4
6

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(139 citation statements)
references
References 32 publications
9
120
4
6
Order By: Relevance
“…Previous studies have suggested that nitroglycerin activates capsaicin sensitive sensory nerves to release CGRP (Wei et al, 1992;Hu et al, 1999;Zhou et al, 2001a;Du et al, 2004;Ghatta and O'Rourke, 2006). The present results showed that nitroglycerin caused a concentration-dependent relaxation and a depressor effect, concomitantly with an increase in the release of CGRP in isolated rat thoracic aorta and in the concentration of CGRP in plasma.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Previous studies have suggested that nitroglycerin activates capsaicin sensitive sensory nerves to release CGRP (Wei et al, 1992;Hu et al, 1999;Zhou et al, 2001a;Du et al, 2004;Ghatta and O'Rourke, 2006). The present results showed that nitroglycerin caused a concentration-dependent relaxation and a depressor effect, concomitantly with an increase in the release of CGRP in isolated rat thoracic aorta and in the concentration of CGRP in plasma.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies have suggested that nitroglycerin can evoke the release of CGRP from capsaicin-sensitive sensory nerves (Wei et al, 1992;Hu et al, 1999;Zhou et al, 2001a;Du et al, 2004;Ghatta and O'Rourke, 2006). We and others have also shown that CGRP mediates the depressor effect and vasodilation produced by nitroglycerin via the cGMP pathway (Zhou et al, 2001a;Booth et al, 2000), and that the decreased depressor effect of nitroglycerin in tolerant states is also related to a decrease in CGRP release (Oroszi et al, 1999;Zhou et al, 2001b;Ghatta and O'Rourke, 2006).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In vivo experiments using a rat model of endotoxicosis have shown that the early hypotension and the loss of vascular responsiveness to noradrenaline occurring within the first 1 h of shock was dependent on NO production and apparently involved the activation of cNOS in either endothelial or neural cells (Wright et al, 1992;Szabo et al, 1993). Some studies have shown that NO appears to increase CGRP release from perivascular nerves in cerebral arteries (Wei et al, 1992), and microvessels in skin (Holzer & Jocic, 1994;Hughes & Brain, 1994;Kajekar et al, 1995) by observation of blood flow in response to a CGRP receptor blocker. On the other hand, several studies have indicated that CGRP does not account for vasodilatation in response to NO (Ralevic et al, 1992;Ayajiki et al, 1994;Faraci & Breese, 1994;Brian et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…and is implicated in the pathogenesis of migraine by activating trigeminovascular fibers and causing release of CGRP [39,40]. NO is synthesized from L-arginine by NO synthase.…”
Section: Nitric Oxide Antagonismmentioning
confidence: 99%